2020
DOI: 10.1037/ccp0000600
|View full text |Cite
|
Sign up to set email alerts
|

Treatment receipt patterns among individuals with co-occurring posttraumatic stress disorder (PTSD) and substance use disorders.

Abstract: Objective: To determine latent classes of treatment receipt among people with comorbid posttraumatic stress disorder (PTSD) and substance use disorder (SUD) and describe each class by demographics, disease characteristics, and psychiatric diagnoses. Method: Participants were National Epidemiologic Survey on Alcohol and Related Conditions-III respondents with lifetime PTSD and SUD (n ϭ 1,349; mean age 40.3; 62.5% female; 30.9% non-White or Hispanic-White). Cross-sectional data were collected using the DSM-5 Alc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 54 publications
(77 reference statements)
0
12
1
Order By: Relevance
“…Studies conducted in SUD clinical sites showed substantially larger effects in five within-group models ( g s = 0.48–1.01) and three between-group models ( g s = 0.55–1.11), with six of the eight significant outcomes pertaining to SUD. It is possible that patients enrolled through SUD treatment clinics participated in additional SUD programming that was helpful to them and/or they had more severe substance use profiles (see Simpson et al, 2020 ) and thus had more room for improvement. Additionally, clinicians at SUD treatment clinics likely have more experience treating individuals with SUD (with or without PTSD) than those in university or laboratory settings where community-based recruiting was the norm.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Studies conducted in SUD clinical sites showed substantially larger effects in five within-group models ( g s = 0.48–1.01) and three between-group models ( g s = 0.55–1.11), with six of the eight significant outcomes pertaining to SUD. It is possible that patients enrolled through SUD treatment clinics participated in additional SUD programming that was helpful to them and/or they had more severe substance use profiles (see Simpson et al, 2020 ) and thus had more room for improvement. Additionally, clinicians at SUD treatment clinics likely have more experience treating individuals with SUD (with or without PTSD) than those in university or laboratory settings where community-based recruiting was the norm.…”
Section: Discussionmentioning
confidence: 99%
“…These studies were excluded from the primary between-group analyses but were included in sensitivity analyses in the trauma-focused vs. all comparators models. To isolate the effects of trauma-focused treatments involving empirically supported PTSD treatment components (CPT: Simpson et al, 2020 ; Vujanovic personal communication; PE 4 : Back et al, 2019 ; Foa et al, 2014 ; Ruglass et al, 2017 ) relative to the most rigorous comparators (manualized SUD), a set of sensitivity analyses involving only those studies were conducted.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations